Three new species of Hawaiian moths from Kahoolawe island (Lepidoptera: Crambidae & Coleophoridae) - Medeiros, Matthew J; Adamski, David (Zootaxa, 2012)
Three new species of Hawaiian Lepidoptera are described herein: Pigritia uuku sp. nov. (Coleophoridae: Blastobasinae), Orthomecyna keoniae sp. nov. (Crambidae), and Tamsica kawikae sp. nov. (Crambidae) from Kahoolawe Island.